Scan - Sellars, Nina (Photomediations Machine, 2013)
Scan offers an interactive and playful narrative where audience can use their mobile phones to scan a QR barcode located on drawing of a skull where tumour, the interaction takes the audience to the actual MRI 'scan' of her brain.